2015
DOI: 10.1097/fpc.0000000000000102
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic T-lymphocyte antigen 4 gene polymorphism influences the incidence of symptomatic human cytomegalovirus infection after renal transplantation

Abstract: These results suggested that CTLA4 variants might be involved in the clinical manifestation of HCMV diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The expression of alternatively spliced flCTLA4 and sCTLA4 isoforms are influenced by the CTLA4 5 0 -upstream regulatory region and 3 0 -untranslated region gene polymorphisms (37,40,41). We have reported four noncoding region SNPs in the 5 0 -upstream regulatory region at positions À318, À658, À1147, and À1661, one SNP þ49 A>G (rs231775) in exon 1, and in the 3 0 -untranslated region noncoding region consisting of one SNP þ6230 A>G (rs3087243) (21). The noncoding region variants of CTLA4 gene may result in abnormal alternative splicing.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The expression of alternatively spliced flCTLA4 and sCTLA4 isoforms are influenced by the CTLA4 5 0 -upstream regulatory region and 3 0 -untranslated region gene polymorphisms (37,40,41). We have reported four noncoding region SNPs in the 5 0 -upstream regulatory region at positions À318, À658, À1147, and À1661, one SNP þ49 A>G (rs231775) in exon 1, and in the 3 0 -untranslated region noncoding region consisting of one SNP þ6230 A>G (rs3087243) (21). The noncoding region variants of CTLA4 gene may result in abnormal alternative splicing.…”
Section: Discussionmentioning
confidence: 96%
“…The detection of genetic variants of the CTLA4 polymorphic markers rs231775, rs5742909, rs11571317, rs16840252, rs4553808, and rs3087243 were performed by polymerase chain reaction (PCR) followed by restriction fragment length polymorphism (RFLP) analysis using primer sequences and restriction enzymes as reported elsewhere (21). To validate the results from PCR-RFLP and for quality control, almost 15% of the samples were randomly selected for regenotyping along with DNA sequencing, and the results were checked for concordance.…”
Section: Genetic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The significance of the association of LILRB1 SNPs with HCMV disease is that it may be useful as part of a collection of biomarkers used to determine the relative risk for patients after receiving a transplant and to guide prophylactic use of antivirals in these patients. Many studies have investigated genetic influences on the immune response to HCMV; the genes implicated in modulating the control of HCMV after transplantation include IL-28B, CCL8, several microRNA, CLTA4, TLR9, DC-SIGN, and, most relevant to NK cells, NKG2C and KIRs (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56). Further studies with additional cohorts could be useful to pinpoint the SNPs with the best correlation and to explore the relationship to the sequence of UL18 within each patient.…”
Section: Genotyping Of Transplant Patientsmentioning
confidence: 99%
“…Recently, It has been reported that the genetic variants of host genome may affect clinical manifestation of symptomatic HCMV infections after renal transplantation [11]. In the present study, we hypothesized that the variations in Host Micro-RNA genes may be associated with clinical manifestation of symptomatic HCMV infection by modulating miRNA expression, maturation or miRNA-mRNA interaction.…”
Section: Introductionmentioning
confidence: 95%